The political economy of monetarism (2007)
It is always a double-edged compliment to characterize an idea as fashionable. The description tends to suggest impermanence and fragility, as if the idea in question could be shrugged off as a topical irrelevance. In the case of monetarism in the 1970s and 1980s, this danger was particularly acute. Many of its detractors found that the sharpest critical approach was to admit that it had gained widespread support, but to imply that such support fluctuated with the ebb and flow of opinion, and made no real difference to economic knowledge.1 This sort of attack was unfair. Certain propositions branded as ‘monetarist’ were not, in fact, distinctive of any school of thought, but formed part of the core of received economic theory. Moreover, many distinctively monetarist themes, far from being an evanescent response to the inflationary excess of the 1970s, had been recognized in one form or another for decades or even centuries.